English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

cos xcos(x – y) + sin xsin(x – y)

2006-11-06 04:12:28 · 4 answers · asked by jonesin_am 1 in Science & Mathematics Mathematics

4 answers

= cosx[cosxcosy+sinxsiny]+sinx[sinxcosy-cosxsiny]

= (Cosx)^2cosy+cosxsinxsiny+(sinx)^2cosy-cosxsinxsiny

= (Cosx)^2cosy + (Sinx)^2cosy

= Cosy [ (cos)x^2 + (sinx)^2]

= Cos(y)

2006-11-06 04:25:31 · answer #1 · answered by AMTV 3 · 0 0

cos(A-B) = cosAcosB + sinAsinB

here A=x, B= x-y

A-B = x-(x-y) = y

Answer Cos(A-B) = cosy

2006-11-06 12:21:44 · answer #2 · answered by vnav_in 2 · 0 0

Beats me!!

2006-11-06 12:19:54 · answer #3 · answered by gone.forever 2 · 0 0

cosAcosB+sinAsinB=cos(A-B)
=cos(x-x+y)
=cosy

2006-11-06 12:27:36 · answer #4 · answered by raj 7 · 0 0

fedest.com, questions and answers